Efeitos de uma desintegrina recombinante de Bothrops alternatus, DISBA-01, em células precursoras miogênicas (CPM) - Pedretti, Ana Carolina Elias (Universidade Federal de São Carlos, 2009)
Disintegrins are toxins commonly found in snake venoms whose biological effects occour upon interaction with surface receptors known as integrins. DisBa-01, an RGD disintegrin isolated from a cDNA library made with mRNAs from the venom gland of Bothrops alternatus, bears anti-metastatic, anti-angiogenic and anti-thrombotic activity in nude mice, partially mediated by interaction with integrin _v_3. Studies with Wistar rats also show that protein has angiogenic activity during regeneration after surgery. The objectives of this study were to evaluate the effects of DisBa-01 on adhesion, deadhesion and proliferation of C2C12 myoblasts and evaluate the electrophoretic profile of secreted proteins of DisBa-01-treated cells. Myoblasts (103 cells/well) were incubated with five concentrations of DisBa-01 under different incubation times and adhesion substracts (plastic, collagen type I or fibronectin). The supernatant was collected for 2DE analysis and the cells were quantified. Also, flow cytometry was used to evaluate the expression of integrins (_2, _4, _5, _v, _v_3, _1 and _4). DisBa-01 inhibited adhesion to fibronectin in high concentration (1000nM) and to collagen type I in all tested concentrations, but did not detach cells from collagen or fibronectina matrix nor affected myoblast proliferation. Flow cytometry showed that integrins _v and _1 were present. 2DE analysis points to an increase of secreted proteins, mainly in higher DisBa- 01 concentration (1000nM). In conclusion, C2C12 myoblasts are sensitive to DisBa-01, suggesting this protein initiates a sinalization cascade mediated by integrins, which modifies protein expression and secretion.
Keywords: Biologia molecular; Células precursoras miogênicas; DisBa-01; Integrinas; Myogenic precursor cells; Integrins; CIENCIAS BIOLOGICAS::GENETICA